Econometric analysis of the impact of fisheries in the Surkhan-darda region on the region’s gross domestic product - Ochildi Kurbonovich Khatamov; Odil Jumanazarovich Davranov (THE INNOVATION ECONOMY, 2026)
This article studies the impact of fish production volume on the Gross Regional Product (GRP) of the Surkhandarya region using econometric analysis. Based on statistical data, a linear regression model was developed, which revealed a strong positive relationship between fish production and the GRP. The results confirm that the fishery sector is an important factor in the economic growth of the Surkhandarya region.